2018
DOI: 10.33588/fem.211.927
|View full text |Cite
|
Sign up to set email alerts
|

Prevalencia y factores asociados a publicar artículos científicos durante la residencia médica en Perú

Abstract: Aim. To determine the prevalence and the factors associated with the publication of scientifi c articles in medical residents of Peru. Subjects and methods. Cross-sectional analytical study using the data obtained by the National Survey for Resident Physicians 2016 (ENMERE-2016), carried out virtually during June 2016. Population: physicians who live in a university in Peru. Sample: residents who voluntarily participated in ENMERE-2016. Outcome of interest: have published at least one scientifi c article. Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
1
8
0
5
Order By: Relevance
“…The frequency of publications in our study is similar to that found in a study for physicians of the residency program [1]. However, both studies are based on self-reported information, so this indicator may be overestimated.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The frequency of publications in our study is similar to that found in a study for physicians of the residency program [1]. However, both studies are based on self-reported information, so this indicator may be overestimated.…”
Section: Discussionsupporting
confidence: 84%
“…Scientific research is an essential component in the training of health professionals, since its practice generates a better understanding of clinical management and, consequently, improves the healthcare provided to patients [1].…”
Section: Introductionmentioning
confidence: 99%
“…Estudios previos en residentes de Perú encontraron que publicar artículos científicos [34] y formarse en un ambiente que promueve la realización de investigación [35] se asocian a una mayor satisfacción con su formación como residente. Así, la posibilidad de realizar investigación fue considerada como importante para la elección de la especialidad.…”
Section: Elección Y Preferencias De La Especialidad Médicaunclassified
“…In addition, funding promotes the training of human resources in research and provides monetary support for publications [ 26 ]. Additionally, salaries for research teachers, improvements in research infrastructure, and payments to external consultants are associated with an increase in scientific production in health sciences [ 27 ].…”
Section: Introductionmentioning
confidence: 99%